Pelatihan Dasar Pemrograman Dasar Python Learning Siswa SMK Pembina Menggunakan Perangkat Mobile - Poetra, M. Andika P; Darsin, Darsin; Lismaini, Lismaini; Susilowati, Endang; Setiono, Setiono (Journal Of Human And Education (JAHE), 2024)
Programming languages ​​are a must-have knowledge apart from hardware in informatics. There are still many students at Pembina Tulang Bawang Vocational School who do not have computers or laptops to use as devices and have minimal understanding of syntax, variables and functions, as well as understanding algorithms and programming logic. The aim of this activity is to provide training in the Python programming language using mobile to vocational school students so that it is hoped that they can provide education and improve and develop students' skills and creativity in using the programming language practically and effectively. The method involved lectures, presentations and practicums, which were attended by 22 students consisting of 10 class X students and 12 class XI students. Evaluation is carried out through an initial evaluation process and final evaluation using a quiz. The results of the training showed an increase in understanding of 35%. This shows that there was an increase in students' understanding of the material that was provided during the training regarding the use of the Pycode application which can be used to carry out Python programming using mobile devices.